2021
DOI: 10.1111/1756-185x.14078
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of baseline laboratory findings of macrophage activation syndrome complicating systemic juvenile idiopathic arthritis and multisystem inflammatory syndrome in children

Abstract: Aims Recently, multisystem inflammatory syndrome in children (MIS‐C) has been recognized in association with coronavirus disease 2019 as a cytokine storm syndrome. MIS‐C presents with symptoms similar to Kawasaki disease and macrophage activation syndrome (MAS). We aimed to better understand this cytokine storm syndrome by comparing the initial laboratory findings of MIS‐C and MAS. Methods Patients who were diagnosed with MAS due to systemic juvenile idiopathic arthritis in our clinic between March 2002 and No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 25 publications
0
27
1
Order By: Relevance
“…It is characterized by unremitting fever, hepatosplenomegaly, hyperferritinemia, pancytopenia, hepatic dysfunction, coagulopathy, and encephalopathy [ 34 ]. Even though most of the laboratory findings in MIS-C suggest a MAS-like cytokine storm, ferritin levels are higher and fibrinogen levels are lower in patients with MAS [ 20 , 21 ]. During the diagnosis of sJIA, presence of higher levels of ferritin and lower levels of fibrinogen were regarded as early warning signs of an impending MAS [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is characterized by unremitting fever, hepatosplenomegaly, hyperferritinemia, pancytopenia, hepatic dysfunction, coagulopathy, and encephalopathy [ 34 ]. Even though most of the laboratory findings in MIS-C suggest a MAS-like cytokine storm, ferritin levels are higher and fibrinogen levels are lower in patients with MAS [ 20 , 21 ]. During the diagnosis of sJIA, presence of higher levels of ferritin and lower levels of fibrinogen were regarded as early warning signs of an impending MAS [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, displaying the major clinical and laboratory differences of MIS-C is critical for making a proper differential diagnosis. The studies comparing MIS-C with classical KD [ 5 , 6 , 16 20 ] or MAS [ 20 , 21 ] are restricted with small sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…The patients with MIS‐C had higher absolute neutrophil counts and C‐reactive protein (CRP) values but lower absolute lymphocyte counts at the time of diagnosis. Left ventricle ejection fraction (LVEF) was significantly lower in the patients with MIS‐C 10 …”
Section: Methodsmentioning
confidence: 99%
“…A male dominance among the patients was shown in several studies. [10][11][12] A systematic review evaluating 917 MIS-C patients showed that the median age of the patients was 9.3 years, and 56.8% of the cases were males. 13 Similarly, male/female ratio was 1.37:1, and the median age was 7.5 years in another systematic review including 992 MIS-C patients.…”
Section: Epidemiologymentioning
confidence: 99%